Microbiome-Related Indole and Serotonin Metabolites are Linked to Inflammation and Psychiatric Symptoms in People Living with HIV. (September 2022) - Vadaq, Nadira; Zhang, Yue; Meeder, Elise; Van de Wijer, Lisa; Gasem, Muhammad Hussein; Joosten, Leo AB; Netea, Mihai G; de Mast, Quirijn; Matzaraki, Vasiliki; Schellekens, Arnt; Fu, Jingyuan; van der Ven, André JAM
Background: People living with HIV (PLHIV) exhibit dysregulation of tryptophan metabolism. Altered gut microbiome composition in PLHIV might be involved. Mechanistic consequences within the 3 major tryptophan metabolism pathways (serotonin, kynurenine, and indoles), and functional consequences for platelet, immune and behavioral functions are unknown. We investigated plasma tryptophan metabolites, gut microbiome composition, and their association with platelet function, inflammation, and psychiatric symptoms. Methods: This study included 211 PLHIV on long-term antiretroviral treatment (ART). Plasma tryptophan pathway metabolites were measured using time-of-flight mass spectrometry. Bacterial composition was profiled using metagenomic sequencing. Platelet reactivity and serotonin levels were quantified by flowcytometry and ELISA, respectively. Circulating inflammatory markers were determined using ELISA. Symptoms of depression and impulsivity were measured by DASS-42 and BIS-11 self-report questionnaires, respectively. Results: Plasma serotonin and indole metabolites were associated with gut bacterial composition. Notably, species enriched in PLHIV were associated with 3-methyldioxyindole. Platelet serotonin concentrations were elevated in PLHIV, without effects on platelet reactivity. Plasma serotonin and indole metabolites were positively associated with plasma IL-10 and TNF-α concentrations. Finally, higher tryptophan, serotonin, and indole metabolites were associated with lower depression and anxiety, whereas higher kynurenine metabolites were associated with increased impulsivity. Conclusion: Our results suggest that gut bacterial composition and dysbiosis in PLHIV on ART contribute to tryptophan metabolism, which may have clinical consequences for immune function and behavior.